The Role of the Elderlyin Enhancing the Feeling of Optimism and Hppiness as Preceived by University Students in Palestine - Katlo, Kamel; Taraweh, Rami (Jordan Journal of Social Sciences, 2020)
The aim of the study is to identify the role of the elderly in promoting a sense of optimism and happiness as perceived by university students according to several variables (gender, level of education, health status of the parents). The study population consists of 18361 Palestinian university students studying at the following Palestinian universities: (Hebron University, Palestine Polytechnic, Jerusalem Open / Hebron Branch) To achieve the objectives of the study, a random sample of (500) students was selected, and applied on them the scale of optimism prepared by the researchers, and the Oxford List of Happiness (OHI). The researchers used the analytical descriptive approach and came out with the following outcomes:• The role of the elderly in promoting a sense of optimism in the university students was high. and that their role in promoting happiness was moderate.• No statistically significant differences in the role of the elderly in promoting the degree of optimism and happiness as perceived by the university students according to the different variables (gender, educational level, and the health status of the father).• There are statistically significant differences in the role of the elderly in promoting the sense of optimism as seen by the university students concerning the following variables: (general health status of the parents, and the level of education).The results were discussed in light of the theoretical framework and the previous studies and some recommendations were acknowledged.